Consumo de diclofenaco, naproxeno e ibuprofeno en un establecimiento farmacéutico ubicado en el departamento de Piura enero – diciembre 2015 - Aguirre Acevedo, Yvan William (2017)
For this report, it was considered the registration of sales of diclofenac, naproxen and ibuprofen in a pharmaceutical establishment located in the department of Piura January - December 2015. For this reason, the data of the units dispensed from diclofenac 50 mg (Tanderil 50 mg tab, diclofenac 50 mg tab Genfar and Deflamat 50 mg cap), naproxen 550 mg (Aflamax 550 mg tab, Apronax 550 mg tab, Intramuscular administration of ibuprofen 400 mg (Doloflam extra strong 400 mg tab, Dolonet forte 400 mg soft tab, Doloral 400 mg tab, Fredol 400 mg tab, Gofen 400 mg Soft drink, Ibaliv 400 mg soft capsule and ibuprofen 400 mg tab Farmindustria) which were obtained from the database of the pharmaceutical establishment, determining the monthly and annual demand of the selected drugs; Being thus it was found that there is a great demand of these products in their different commercial equivalents, reason why the NSA of greater consumption was naproxen 550 mg with an annual consumption of 26 238 units dispensed and an annual cost of S /. In the same way, the lowest-consumption NSAID was diclofenac 50 mg, with an annual consumption of 3,762 units dispensed and an annual cost of S /. 1 674